Crisis, censura y búsquedas de la industria del cine mexicano en los años cincuenta. El caso de Sombra verde de Producciones Calderón - Mino Gracia, Fernando (El Colegio de México, A.C., 2019)
The film Sombra Verde (Roberto Gavaldón, 1954), produced by the brothers Pedro and Guillermo Calderón, was a failed attempt to enter the English-speaking market through a film of “high artistic quality” featuring a Hollywood star. Through an analysis of the documents held in the Producciones Calderón archives, this article narrates the history of the filming and distribution of this movie, emphasizing the tensions and negotiations that Mexican film producers engaged in with the government institutions responsible both for film censorship and financing. Examining this case allows us to analyze the strategic importance of the domestic film industry, shaped by government censorship, in the construction of subjectivities during the 1950s.